Sistema de guía, navegación y retroalimentación para un misil tierra-aire a través de sistemas híbridos - Limón Díaz, Pedro Antonio (2016)
Objectives and study method: This thesis aims to design and to develop a platform that is capable to guide, control a system orientation as well as the position for a missile. The system designed can be also extrapolated to an unmanned aerial vehicle. The platform designed will help to generate tools to define the orientation and position of a vehicle by acquiring data from an inertial measurement unit in real time. To confirm the platform operation, a co-simulation technique Hardware-InThe-Loop is used. By using this technique, it is possible to divide the platform into the following modules: 1) Sensor module. This module is composed by an accelerometer, gyroscope, magnetometer, barometer, temperature sensor (that are co-integrated in the same board) and an IR camera. 2) Flight computer module. This module has a distributed system architecture. One side is composed by a commertial development FPGA board for data acquisition, a personal computer for processing and displaying data results. Contributions and conclusions: The developing process is to perform a simulation that, separately, communicates the sensor module block with the flight computer module. Once confirmed the data acquisition and the processes, we will proceed to co-integrate all the algorithms into a main one and test the platform with all the instruments. Additionally, we add a communication module that is co-integrated with a radio frequency transceiver to reinforce a wireless communication. A detailed process to implement the embedded system within the FPGA board is included. The specifications for each element used as the sensor, flight computer and communication modules with a comprehensive description of the system generation are shown. Finally, the results of the test, conclusions and recommendations for future work are addressed.